Melanoides tuberculatus (Müller, 1774): a new threat to the conservation of native aquatic species in Sergipe, Brazil. - Souto, Leandro de Sousa; Brito, Marcelo Fulgêncio Guedes; Rosa, Leonardo Cruz da (Scientia Plena, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–> Nesse trabalho, a presença do molusco exótico invasor Melanoides tuberculatus é registrado pela primeira no Estado de Sergipe. O fato agravante é que sua ocorrência foi detectada em duas unidades de conservação do Estado, uma na região costeira e outra no semi árido sergipano. Foram coletados 227 indivíduos desse molusco na Lagoa Azul, a maior lagoa da APA Litoral Sul e nas margens do rio São Francisco, em uma reserva de Caatinga. A presença dessa espécie exótica invasora é uma ameaça a biodiversidade local bem como pode tornar-se um problema de sanidade ambiental, uma vez que esse molusco também pode ser hospedeiro de trematódeos exóticos, como Centrocestus formosanus (Trematoda: Heterophyidae). <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–> In this study the occurrence of the exotic snail Melanoides tuberculatus was registered for the first time in Sergipe State, Brazil, in two conservation areas. In total, 227 snails were collected from rivers and a lake in both coastal and semi-arid regions (Lagoa Azul and São Francisco river). Owing to the fact that M. tuberculatus can act as an intermediate host of Centrocestus formosanus (Trematoda: Heterophyidae), the occurrence of this exotic species is a threat to local biodiversity in addition to becoming a serious problem of environment sanitarity.